Petroleum Pumps' Current and Vibration Signatures Analysis Using Wavelet Coherence Technique. (12th June 2013) - Shnibha, Rmdan; Albarbar, Alhussein
Abstract : Vibration analysis is widely used for rotating machinery diagnostics; however measuring vibration of operational oil well pumps is not possible. The pump's driver's current signatures may provide condition-related information without the need for an access to the pump itself. This paper investigates the degree of relationship between the pump's driver's current signatures and its induced vibration. This relationship between the driver's current signatures (DCS) and its vibration signatures (DVS) is studied by calculating magnitude-squared coherence and phase coherence parameters at a certain frequency band using continuous wavelet transform (CWT). The CWT coherence-based technique allows better analysis of temporal evolution of the frequency content of dynamic signals and areas in the time-frequency plane where the two signals exhibit common power or consistent phase behaviour indicating a relationship between the signals. This novel approach is validated by experimental data acquired from 3 kW petroleum pump's driver. Both vibration and current signatures were acquired under different speed and load conditions. The outcomes of this research suggest the use of DCS analysis as reliable and inexpensive condition monitoring tool, which could be implemented for oil pumps, real-time monitoring associated with condition-based maintenance (CBM) program.